THE EFFECT OF NON-FINANCIAL REPORTING ON INVESTMENT DECISION-MAKING AMONG RETAIL INVESTORS (IITM Journal of Business Studies, 2025)
This paper aims to examine the current  behavior qua retail investors regarding India’s  non-financial reporting and how non-financial  reporting has impacted their decisions.  The study further delves into the influence  of various factors viz-a-viz non-financial  reporting and the investment decision. Non financial reporting has been represented by  the standardized Business Responsibility and  Sustainability Report. During the investigation  and preparation of the present paper, the author  has taken three independent variables and one  dependent variable. The independent variables  taken by the author are environmental variables,  social variables, and governance as the third  variable, whereas the responding variable is the  investment decision. The author tries to collect  data by distributing questionnaires among the  retail investors who have applied for securities  for less than Rs. 2,00,000/- with a sample size of  500 respondents.
Keywords: Environmental, Social, and Governance (ESG) Disclosure; Investment Decision; Retail Investors; Non-Financial Reporting